2019
DOI: 10.1097/hjh.0000000000001826
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship between thyroid stimulating hormone and hypertension risk in euthyroid individuals

Abstract: The current study provides strong evidence for the dose-response relationship between serum TSH level and hypertension risk in euthyroid individuals. Euthyroid individuals with higher normal TSH level are at higher risk of developing hypertension than those with lower normal TSH level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…Since blood pressure is an independent risk factor for cardiovascular diseases, the elevated blood pressure may mediate or further aggravate the harm of SCH on cardiovascular health ( 9 , 10 , 14 ). Some observational studies including one our study have also suggested an obviously positive relationship between TSH level and hypertension risk among euthyroid individuals, which supports a possibly causal role of elevated TSH level in the development of hypertension ( 16 18 ). However, the relationship between thyroid dysfunction and hypertension is still controversial, and the causal relationship between SCH and hypertension has not been well established ( 9 , 19 , 20 ).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Since blood pressure is an independent risk factor for cardiovascular diseases, the elevated blood pressure may mediate or further aggravate the harm of SCH on cardiovascular health ( 9 , 10 , 14 ). Some observational studies including one our study have also suggested an obviously positive relationship between TSH level and hypertension risk among euthyroid individuals, which supports a possibly causal role of elevated TSH level in the development of hypertension ( 16 18 ). However, the relationship between thyroid dysfunction and hypertension is still controversial, and the causal relationship between SCH and hypertension has not been well established ( 9 , 19 , 20 ).…”
Section: Introductionsupporting
confidence: 76%
“…Secondly, the modest impact of TSH on blood pressure may conceal the effect of LT4 therapy. Previous studies including one our study have shown a statistically significant relationship between TSH and blood pressure although with less dramatic coefficient, suggesting that decreasing TSH level through LT4 therapy may only have a modest effect on blood pressure ( 16 18 ). At last, many SCH participants enrolled in these RCTs were normotensive, which could interfere the blood pressure-lowering effect of LT4 therapy.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, most clinical studies focused on the relationship between TSH and blood pressure levels . In 2018, the meta‐analysis of He et al showed the relationship of TSH with increased clinic systolic and diastolic blood pressures, but it could not explain the high heterogeneity in the results of analysis ( I 2 = 90%) . In addition, many recent clinical studies did not support the results .…”
Section: Introductionmentioning
confidence: 99%
“…is meta-analysis indicates that only subclinical hypothyroidism is associated with increased SBP and DBP, whereas subclinical hyperthyroidism is not. A recent publication by He et al [30] conducted another metaanalysis showing a dose-response relationship between serum TSH level and hypertension risk even in euthyroid individuals, suggesting individuals with higher normal TSH level are at higher risk of developing hypertension than those with lower normal TSH level. Reports from Japan [5] and Germany [6,31] demonstrated this phenomenon existed despite countries of different iodine supply in food (iodinereplete in Japan while iodine-deficient in Germany) as well as prevalence of hypertension (higher in Japan than Germany).…”
mentioning
confidence: 99%